2018
DOI: 10.3389/fmicb.2018.02105
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic N2 Fixation and Grain Yield of Endangered Kersting's Groundnut Landraces in Response to Soil and Plant Associated Bradyrhizobium Inoculation to Promote Ecological Resource-Use Efficiency

Abstract: Kersting's groundnut (Macrotyloma geocarpum Harms) is a neglected, endangered food and medicinal legume in Africa. Efforts to harness the benefits of the legume-rhizobia symbiosis have focused on few major legumes to the neglect of underutilized ones such as Kersting's groundnut. This study assessed plant growth, N-fixed and grain yield of five Kersting's groundnut landraces in response to inoculation with Bradyrhizobium strain CB756 at two locations in the Northern Region of Ghana. The transferability of cowp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 46 publications
4
36
1
Order By: Relevance
“…In this study, the difference between the δ 15 N value of reference plants and those of the test cowpeas was sufficiently large (>+2‰) [11], and therefore al- (Table S1). These findings are consistent with previous studies which found that high soil N inhibits N 2 fixation in symbiotic legumes [33], and that marginal differences in soil N between locations altered the δ 15 N of symbiotic Kersting's groundnut [10]. The variations in shoot δ 15 N values within genotypes and between locations were expectedly accompanied by differences in the percent of N derived from symbiotic N 2 fixation (%Ndfa) by the test cowpeas in this study.…”
Section: Symbiotic Performance Of Field-grown Cowpea Genotypessupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the difference between the δ 15 N value of reference plants and those of the test cowpeas was sufficiently large (>+2‰) [11], and therefore al- (Table S1). These findings are consistent with previous studies which found that high soil N inhibits N 2 fixation in symbiotic legumes [33], and that marginal differences in soil N between locations altered the δ 15 N of symbiotic Kersting's groundnut [10]. The variations in shoot δ 15 N values within genotypes and between locations were expectedly accompanied by differences in the percent of N derived from symbiotic N 2 fixation (%Ndfa) by the test cowpeas in this study.…”
Section: Symbiotic Performance Of Field-grown Cowpea Genotypessupporting
confidence: 92%
“…Of the many techniques used to estimate legume symbiotic performance, the 15 N natural abundance has so far been useful in quantifying N 2 fixation in field-grown legumes [8] [9]. This technique requires the estimation of the isotopic fractionation associated with N 2 fixation in the legume (so called B value), and the selection of reference plants to estimate the soil N uptake by the legume [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…According to farmers, Kersting's groundnut helps improve the fertility of the soil, thereby reducing the cost of fertilizer inputs in crop farming. This is certainly due to the nodulation property of the crop for symbiotic nitrogen fixation [16,46] leading to the positive contribution of legume crops in the yield improvement of associated crops [47][48][49].…”
Section: Kersting's Groundnut Production Systems In Burkina Faso and mentioning
confidence: 99%
“…Kersting’s groundnut is a drought-tolerant legume (5) and is also adapted to growth in N-deficient soils due to its ability to fix atmospheric N 2 when in symbiosis with soil bacteria called rhizobia. The symbiotic process leads to a high supply of N to the plant and the production of substantial grain yield without external chemical inputs (6, 7). Despite its N 2 -fixing ability, as well as its nutritional and medicinal benefits (2, 8, 9), Kersting’s groundnut is labeled as an orphan crop and is endangered due to neglect by farmers and researchers (10).…”
Section: Introductionmentioning
confidence: 99%
“…These sets of information have contributed significantly to the current progress in tapping the benefits of the legume-rhizobium symbiosis for crop production, especially through the use of inoculant formulations with superior N 2 -fixing rhizobial strains (20, 21). However, much remains to be done, as inoculation failures are often encountered when inoculant strains are introduced into new environments (7, 20, 22), thus stressing the need to bioprospect for effective and highly adapted indigenous rhizobial strains for grain legume nodulation in their native environments. Although rhizobial population studies have contributed significantly to our current understanding of the factors influencing their distribution and survival in diverse environments, it is their N 2 -fixing efficacy that is often considered a prerequisite for their selection as strains for inoculant production.…”
Section: Introductionmentioning
confidence: 99%